Hidden unity in nature's laws - Taylor, John C. 1930- (Cambridge University Press, 2001)
As physics has progressed through the ages it has succeeded in explaining more and more diverse phenomena with fewer and fewer underlying principles. This lucid and wide-ranging book explains how this understanding has developed by periodically uncovering unexpected 'hidden unities' in nature. The author deftly steers the reader on a fascinating path which goes to the heart of physics - the search and discovery of elegant laws which unify and simplify our understanding of the intricate Universe in which we live. Starting with the Ancient Greeks, the author traces the development of major concepts in physics right up to the present day. Throughout, the presentation is crisp and informative and only a minimum of mathematics is used. Any reader with a background in mathematics or physics will find this book a fascinating insight into the development of our fundamental understanding of the world, and the apparent simplicity underlying it.